Effect of the amount of cationic lipid used to complex siRNA on the cytotoxicity and proinflammatory activity of siRNA-solid lipid nanoparticles - Mahmoud S. Hanafy; Huy M. Dao; Haiyue Xu; John J. Koleng; Wedad Sakran; Zhengrong Cui (Elsevier, 2023)
When preparing siRNA-encapsulated solid lipid nanoparticles (siRNA-SLNs), cationic lipids are commonly included to condense and lipophilize the siRNA and thus increase its encapsulation in the SLNs. Unfortunately, cationic lipids also contribute significantly to the cytotoxicity and proinflammatory activity of the SLNs. Previously, our group developed a TNF-α siRNA-SLN formulation that showed strong activity against rheumatoid arthritis unresponsive to methotrexate in a mouse model. The siRNA-SLNs were composed of lecithin, cholesterol, an acid-sensitive stearoyl polyethylene glycol (2000) conjugate, and siRNA complexes with 1,2-dioleoyl-3trimethylammonium-propane (DOTAP), a cationic lipid. The present study was designed to study the effect of the amount of DOTAP used to complex the siRNA on the cytotoxicity and proinflammatory activity of the resultant siRNA-SLNs. A small library of siRNA-SLNs prepared at various ratios of DOTAP to siRNA (i.e., nitrogen to phosphate (N/P) ratios ranging from 34:1 to 1:1) were prepared and characterized, and the cytotoxicity and proinflammatory activity of selected formulations were evaluated in cell culture. As expected, the siRNA-SLNs prepared at the highest N/P ratio showed the highest cytotoxicity to J774A.1 macrophage cells and reducing the N/P ratio lowered the cytotoxicity of the siRNA-SLNs. Unexpectedly, the cytotoxicity of the siRNA-SLNs reached the lowest at the N/P ratios of 16:1 and 12:1, and further reducing the N/P ratio resulted in siRNA-SLNs with increased cytotoxicity. For example, siRNA-SLNs prepared at the N/P ratio of 1:1 was more cytotoxic than the ones prepared at the N/P ratio 12:1. This finding was confirmed using neutrophils differentiated from mouse MPRO cell line. The DOTAP release from the siRNA-SLNs prepared at the N/P ratio of 1:1 was faster than from the ones prepared at the N/P ratio of 12:1. The siRNA-SLNs prepared at N/P ratios of 12:1 and 1:1 showed comparable proinflammatory activities in both macrophages and neutrophils. Additionally, the TNF-α siRNA-SLNs prepared at the N/P ratios of 12:1 and 1:1 were equally effective in downregulating TNF-α expression in J774A.1 macrophages. In conclusion, it was demonstrated that at least in vitro in cell culture, reducing the amount of cationic lipids used when preparing siRNA-SLNs can generally help reduce the cytotoxicity of the resultant SLNs, but siRNA-SLNs prepared with the lowest N/P ratio are not necessarily the least cytotoxic and proinflammatory.